Philippine manufacturers directory. (Pacific Pub. House, 1991)
This directory contains in alphabetical order : a) buyer's guide section where top firms in the manufacturing industry are listed; b) manufacturing directory; c) employment agencies listing; d) transportation and cargo listings for fast shipping of products, and an advertisers' index. Advertisements are illustrated at the end pages.